Acute toxicity of copper (Cu 2+ ) on postlarvae of river prawn Cryphiops caementarius (Natantia, Palaemonidae) - Mendoza-Rodríguez, Raúl (2007)
Copper toxicity is evaluated on the river prawn postlarvae, Cryphiops caementarius, using acute toxicity tests, to determine lethal concentration (96-LC50). The postlarvae were very sensitive to copper with 96-LC50 values of 0,546 mg.l-1. Survival and swimming activity diminish with the increase of copper concentrations. Concentrations of 1,0 and 2,0 mg.l-1 were dangerously pollut- ant (63,3 and 100% mortality for 96 h), concentrations of 0,16 and 0,25 mg.l-1 were tolerable (0% mortality for 48 h).